Emotional Support for Kindergarten Child (Journal Of Educational and Psychological Researches, 2024)
The current research aims to identify the level of emotional support and the significance of the difference in emotional support according to the gender variable (male, female) for the kindergarten children, who were chosen by the simple random sample method for the academic year 2022-2023. Item discrimination and face validity was extracted. The reliability of the research tool was verified by test-retest and Cronbach's alpha methods. Using the retest method, the reliability coefficient reached 0.838, while it reached 0.90 using Cronbach’s alpha method. The number of items in their final form for the emotional support scale was 30. After verifying the validity of the research tool in light of validity and reliability indicators, the tool was applied to the research sample. Then, the data was collected and processed statistically. The current research reached the following result: the members of the current research sample of kindergarten children generally have emotional support. As for the gender variable (male or female), it is found that there is no significance difference between them in this aspect. In light of these results, the researcher presented some recommendations and suggestions, as explained in the fourth chapter.